Possible Mechanisms Involved in the Cooccurrence of Oral Lichen Planus and Hashimoto's Thyroiditis. (4th February 2020) - Wu, Peiyao; Luo, Shuhan; Zhou, Tao; Wang, Rui; Qiu, Xuemei; Yuan, Peiyang; Yang, Yuqing; Han, Qi; Jiang, Lu
Abstract : Oral lichen planus (OLP) is a chronic inflammatory oral mucosal disorder mediated by T cells, with a multifactorial etiology. Hashimoto's thyroiditis (HT) is a common autoimmune disease characterized by hypothyroidism. Although many clinical studies conducted over the past several decades have reported the cooccurrence of OLP and HT, the underlying mechanism remains unclear. This review summarizes potential mechanisms that might be involved in the cooccurrence of OLP and HT. We find that OLP and HT share a common or overlapping pathogenesis in terms of immune, heredity, environmental, and hormonal factors, which might cause cooccurrence. Furthermore, considering the latency of HT, a routine screen for thyroid diseases, particularly HT, is suggested for confirmed OLP patients.